METABOLIC SYNDROME IMPAIRS QUALITY OF LIFE AND FUNCTIONAL STATUS IN PATIENTS WITH FIBROMYALGIA SYNDROME - Akgol, Gurkan; Elbasti, Muhammet Sahin; Gulkesen, Arif; Alkan, Gokhan; Kaya, Arzu; Ulusoy, Hasan (Carbone Editore, 2022)
Introduction: Obesity and insulin resistance are important risk factors for metabolic syndrome (Mets). Studies on Mets frequency and its effects on quality of life in patients with fibromyalgia syndrome (FMS) are inconclusive. We aimed to investigate the frequency of obesity, insulin resistance and Mets in patients with FMS and to examine their effect on quality of life (QoL). Materials and methods: Fifty FMS patients and fifty controls between 20 and 60 ages were included in the study. The diagnosis of Mets was made according to the criteria of the International Diabetes Federation. Insulin resistance was measured using the homeostasis model assessment of insulin resistance (HOMA-IR) method. Fibromyalgia Impact Questionnaire (FIQ) and the Short Form-36 questionnaire (SF-36) were used to evaluate the functional status and QoL. Pain were evaluated on the visual analog scale (VAS). Results: There was no significant difference in BMI values between the groups. Waist circumference was significantly higher in the FMS group (p=0.004). While 28 (56%) patients in the FMS group met the diagnostic criteria for Mets, 9 (18%) patients in the control group met the diagnostic criteria for Mets (p<0.001). Insulin resistance was found in 28 (56%) patients in the FMS group and 19 (38%) patients in the control group (p=0.002). The FIQ score and VAS-pain score were significantly higher in the FMS group (p<0.001). QoL and functional status parameters assessed by SF-36 were significantly lower in the FMS group compared to the control group (p<0.001). While BMI showed significant positive correlations with VAS-pain (p=0.005) and FIQ (p=0.047), it showed significant negative correlations with physical function (p=0.017), emotional limitation (p=0.046), and general health (p=0.01) parameters of the SF-36. HOMA-IR showed a significant positive correlation with waist circumference (p=0.048), but not BMI. Conclusions: The frequency of Mets and insulin resistance are increasing in patients with FMS. As BMI increases, QoL and functional status deteriorate. Increased physical activity and lifestyle changes may be beneficial to improve the QoL by preventing insulin resistance and Mets.
Keywords: Fibromyalgia; metabolic syndrome; obesity; quality of life; QoL